Optimizacija kopolimerizacije akrilatov v emulziji - Lamovec, Vlasta (Kovine zlitine tehnologije, 1998)
A binder for preparation of frontage coating has been synthesized by emulsion polymerization. Properties of the synthesized binder have been compared with those of commercial binder. The properties of frontage coating made from synthesized binder have been compared to the coating made from commercial binder.
Keywords: polimerizacija; poliakrilati; kopolimerizacija; premazi; emulzije